The Investigation of Ecological Citizenship Levels of Teacher Candidates - Ünal, Emre (Asian Journal of Education and Training, 2019)
The aim of this study is to investigate the ecological citizenship of teacher candidates in terms of different variables and to determine the variables influencing the ecological citizenship level. The study group consists of 318 voluntary senior students who study at the departments of Primary School Teaching, Social Studies Teaching, Primary School Mathematics Teaching, Science Teaching and Physical Education and Sports Teaching in the faculty of education at a state university. The data were obtained through Ecological Citizenship Scale developed by Karatekin and Uysal (2018). The study was designed in survey method, which is a quantitative research method. The results of the study showed that the ecological citizenship levels of teacher candidates did not differ significantly in terms of the variables of gender, mother educational attainment level, father educational attainment level, membership to non-governmental organizations and membership to student organizations while significant differences were found in terms of the variables of department and participation in social projects.